Enhanced protein degradation by black soldier fly larvae (Hermetia illucens L.) and its gut microbes - Yu, Yongqiang; Zhang, Jia; Zhu, Fengling; Fan, Mingxia; Zheng, Jinshui; Cai, Minmin; Zheng, Longyu; Huang, Feng; Yu, Ziniu; Zhang, Jibin (Frontiers in Microbiology, 2023)
Black soldier fly larvae (BSFL) can convert a variety of organic wastes into biomass, and its gut microbiota are involved in this process. However, the role of gut microbes in the nutrient metabolism of BSFL is unclear. In this study, germ-free BSFL (GF) and gnotobiotic BSFL (GB) were evaluated in a high-protein artificial diet model. We used 16S rDNA sequencing, ITS1 sequencing, and network analysis to study gut microbiota in BSFL that degrade proteins. The protein reduction rate of the GB BSFL group was significantly higher (increased by 73.44%) than that of the GF BSFL group. The activity of gut proteinases, such as trypsin and peptidase, in the GB group was significantly higher than the GF group. The abundances of different gut microbes, including Pseudomonas spp., Orbus spp. and Campylobacter spp., were strongly correlated with amino acid metabolic pathways. Dysgonomonas spp. were strongly correlated with protein digestion and absorption. Issatchenkia spp. had a strong correlation with pepsin activity. Campylobacter spp, Pediococcus spp. and Lactobacillus spp. were strongly correlated with trypsin activity. Lactobacillus spp. and Bacillus spp. were strongly correlated with peptidase activity. Gut microbes such as Issatchenkia spp. may promote the gut proteolytic enzyme activity of BSFL and improve the degradation rate of proteins. BSFL protein digestion and absorption involves gut microbiota that have a variety of functions. In BSFL the core gut microbiota help complete protein degradation. These results demonstrate that core gut microbes in BSFL are important in protein degradation.